An Overview of Fear of Crime and Its Criminological Significance - De Silva, K. B. N; Dharmasiri, K. S; Buddhadasa, M. P. A. A; Ranaweera, K. G. N. U (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2021)
Fear of crime is a term that refers to an anxious emotional state caused by the belief that one is at risk of criminal victimisation. Before the 1960s, mainstream criminological studies gave inadequate attention to criminal fear. Despite widespread public concern and fear of crime, it was only after early 1960s US crime surveys that the issue gained policy, research, and political attention. Accordingly, it can be identified that the ‘‘Fear of crime’’ is a complex concept that has been debated for an extended period, and it is critical to review its research gaps. The objective of this research is to determine the criminological significance of “fear of crime.” Mixed-method systematic review approaches have been applied for the study: status quo review and rapid review. According to the study, recent research on fear of crime has focused on individual and contextual predictors and the consequences of crime fear; more people have feared crime than become victims. In the most recent research approaches on fear of crime, it is emphasised that perceived risk precedes and causes fear. It has been revealed that the term “fear of victimisation” is more precise than “fear of crime” to clarify criminological studies; most studies and researchers use these terms interchangeably. Furthermore, it is suggested that future research should pay attention to the factors affecting fear of victimisation.